2019
DOI: 10.1371/journal.pone.0218907
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistant bacteria and commensal fungi are common and conserved in the mosquito microbiome

Abstract: The emerging and increasing prevalence of bacterial antibiotic resistance is a significant public health challenge. To begin to tackle this problem, it will be critical to not only understand the origins of this resistance but also document environmental reservoirs of antibiotic resistance. In this study we investigated the possibility that both colony and field caught mosquitoes could harbor antibiotic resistant bacteria. Specifically, we characterized the antibiotic resistant bacterial populations from colon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 54 publications
3
36
0
Order By: Relevance
“…Cockroaches are widespread and live in proximity to humans. Thus, similar to other insects (71), they might represent a public health problem due to their role as potential ARG transmission vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Cockroaches are widespread and live in proximity to humans. Thus, similar to other insects (71), they might represent a public health problem due to their role as potential ARG transmission vectors.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the infected cockroaches successfully transferred the resistant bacterium into water, table eggs (whole uncracked egg surfaces), and other insects, with contamination occurring up to four days following the start of the experiments. For biting insects like spiders [ 103 ], mosquitoes [ 104 ], and bed bugs [ 105 ], the transfer of ARB to humans could occur through insect bites.…”
Section: The Role Of Insects Rodents and Pets In Amr Persistencementioning
confidence: 99%
“…Some research questions involving microbiota modification may call for the use of axenic or gnotobiotic mosquitoes. Antibiotics have been used in such studies until recently, but (i) antibiotics might directly affect the mosquito physiology or vector competence regardless of their impact on the microbiota [ 23 ], (ii) they do not fully clear the mosquito microbiota [ 24 ], and (iii) mosquitoes have been shown to harbor antibiotic-resistant microbes [ 25 ]. Recent developments in the creation of axenic and/or gnotobiotic mosquitoes [ 17 , 26 ] offer promising solutions to these challenges and have revealed a critical role of the microbiota in larval development.…”
Section: Proposed Guidelines For Mosquito Microbiome Researchmentioning
confidence: 99%